Cover Image. Issue 3 (15th March 2018) - Kuzin, Alexander; Smith, Svetlana; Brody, Thomas; Odenwald, Ward F.
Abstract : Cover: The cover image, by Alexander Kuzin et al., is based on the Research Article Structure and cis-regulatory analysis of a Drosophila grainyhead neuroblast enhancer, DOI:10.1002/dvg.23094 .